The Fluorescent Detection of Alkaline Phosphatase Based on Iron Nanoclusters and a Manganese Dioxide Nanosheet - Liang Zhao; Xinyue Liu; Xinwen Zhang; Siyu Liu; Jiazhen Wu (Sensors)
Fluorescent iron nanoclusters are emerging fluorescent nanomaterials. Herein, we synthesized hemoglobin-coated iron nanoclusters (Hb−Fe NCs) with a significant fluorescence emission peak at 615 nm and investigated the inner-filter effect of fluorescence induced by a manganese dioxide nanosheet (MnO2 NS). The fluorescence quenching of Hb−Fe NCs by a MnO2 NS can be significantly reversed by the addition of ascorbic acid. On the basis of fluorescent recovery by ascorbic acid, we proposed a system that consisted of Hb−Fe NCs, a MnO2 NS and ascorbate phosphate, and the proposed system was successfully used for alkaline phosphatase (ALP) detection in the range of 0–20 μg/mL based on the significant fluorescence recovery achieved.